2018
DOI: 10.7567/apex.11.093102
|View full text |Cite
|
Sign up to set email alerts
|

High infield performance and critical temperatures in post-annealed MgB2 films

Abstract: Critical temperatures (Tc) comparable to those of bulk materials were achieved by post-annealing MgB2 thin films grown at a low temperature of 280 °C. The Tc was improved to 36.7 K under annealing conditions of 550 °C for 50 h or more. Under these annealing conditions, a critical current density several tens of times higher at than that of MgB2 wires processed by a powder-in-tube method was achieved at 20 K under 5 T. This is the highest value reported in MgB2 bulk wires and films. Film-based MgB2 is a promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…nonannealed film to 0.18 MA cm −2 , which was approximately 90% lower than that in the self-magnetic field under a magnetic field of 5 T. The decrease in the J c of the annealed sample under a magnetic field of 5 T was approximately 40%, which was significantly lower than that of the nonannealed sample. The MgB 2 film that was annealed at 650 °C exhibited a J c of 1.62 MA cm −2 at 20 K under 5 T. This was not only more than 2.5 times higher than the previous highest J c of 0.64 MA cm −2 for the EBE-prepared MgB 2 films that were annealed at 550 °C in vacuum 12) but also more than 100 times higher than the J c for the PIT-processed wires. 13) The results of our study demonstrated that high-temperature annealing and the Nb protective layer significantly increased the J c of the EBE-prepared MgB 2 thin films under high magnetic fields.…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…nonannealed film to 0.18 MA cm −2 , which was approximately 90% lower than that in the self-magnetic field under a magnetic field of 5 T. The decrease in the J c of the annealed sample under a magnetic field of 5 T was approximately 40%, which was significantly lower than that of the nonannealed sample. The MgB 2 film that was annealed at 650 °C exhibited a J c of 1.62 MA cm −2 at 20 K under 5 T. This was not only more than 2.5 times higher than the previous highest J c of 0.64 MA cm −2 for the EBE-prepared MgB 2 films that were annealed at 550 °C in vacuum 12) but also more than 100 times higher than the J c for the PIT-processed wires. 13) The results of our study demonstrated that high-temperature annealing and the Nb protective layer significantly increased the J c of the EBE-prepared MgB 2 thin films under high magnetic fields.…”
mentioning
confidence: 65%
“…The presence of Nb (110) and MgB 2 (002) peaks in the XRD pattern of the nonannealed films revealed the formation of c-axis oriented MgB 2 thin films. 12) The intensity of the XRD peaks of MgB 2 was low owing to the deposition of the Nb protective layer on MgB 2 film; therefore, the MgB 2 (001) peak was not observed in this study. The XRD pattern of the film that was annealed at 450 °C was not significantly different from that of the nonannealed film.…”
mentioning
confidence: 70%
See 3 more Smart Citations